The time analysis of 110 m hurdle events - Horie, M; Shimizu, S.; Yamamoto, H. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
The purpose of this study was to clarify the pattern of speed changes during the 110m hurdle events. One hundred and five subjects were divided into A group, B group and C group according to record. The speed of each section, the speed ratio compared with a maximum speed and the time ratio were calculated. The results showed that the speed changes of A group has similarity to the previous reports for top hurdlers, though the speed of each section decreased gradually in B group and C group. The correlation coefficient of the latter half, especially in the section from the 7th hurdle to the 9th hurdle, were higher than that of the first half and also the speed in these sections were related to the record particularly. It was found that the speed change of B, and C group were different from that of top-level, and that these results could be applied to the training programs for the Middle-level hurdlers.